Aquaporin-4 Is Downregulated in the Basolateral Membrane of Ileum Epithelial Cells during Enterotoxigenic Escherichia coli-Induced Diarrhea in Mice - Zhang, Di; Yang, Longfei; Su, Weiheng; Zhao, Yuan; Ma, Xin; Zhou, Haizhu; Xu, Bo; Zhang, Kaiqi; Ma, Hongxia (Frontiers in Microbiology, 2018)
Enterotoxigenic Escherichia coli (ETEC) are opportunistic pathogens that colonize the small intestine, produce enterotoxins and induce diarrhea. Some aquaporins (AQPs), such as AQP3 and AQP8, have been reported to participate in diarrhea by decreasing cellular influx in the gastrointestinal (GI) tract. AQP4 is another important water channel in the GI tract, but its role in ETEC-induced diarrhea has not been reported. Here, we demonstrated the potential roles of AQP4 in ETEC-induced diarrhea. Reverse transcription–polymerase chain reaction and western blotting showed that AQP4 was expressed in the mouse ileum, but not in the duodenum or jejunum while immunohistochemical staining showed that AQP4 localized to the basolateral membrane of ileum epithelial cells. Using an ETEC-induced mice diarrhea model, we demonstrated that both AQP4 mRNA level and the AQP4 protein level in the ileum decreased gradually over a time course of seven days. These results suggest that AQP4 plays a role in the pathogenesis of ETEC-induced diarrhea by mediating water transport.